2001
DOI: 10.1021/ef000081k
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Pore Structure of Turkish Coals

Abstract: Pore structure of coal has a great influence on its behavior during mining, preparation, and utilization. Characterization of the pore structure of twelve Turkish coals from different geographic locations and with carbon contents varying between 61 and 84% (on dry ash-free basis) was carried out using different techniques. The volume and area of macropores were determined by mercury intrusion porosimetry. Mesopore volumes and areas were determined by N2 gas adsorption at 77 K using the Barrett−Joyner−Halenda (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
27
0
1

Year Published

2007
2007
2023
2023

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 66 publications
(28 citation statements)
references
References 45 publications
0
27
0
1
Order By: Relevance
“…The figure shows that at 875 C, the variation of reactivity with conversion profiles for all lignite samples has similar trends; it first increases up to a certain conversion, which is different for each lignite sample, then decreases with a further increase in the conversion. The authors explained the reactivity with conversion data of different ranks of coal using the results from a previous study which involved several texture characterization techniques [17] and demonstrated that lignite samples under study possessed micropores of molecular dimensions and that SAXS (Small Angle X-ray Scattering) measurement and carbon dioxide adsorption data indicated that some of these pores were closed and some were opened to larger mesopores and macropores with restricted passages [18]. It is observed that in the initial stages of the gasification disorganized carbon from tars are removed resulting in the opening of inaccessible porosity and then an increase in all sizes of pores which enhance reactivity until up to a certain conversion.…”
Section: Effect Of Coal Rankmentioning
confidence: 99%
“…The figure shows that at 875 C, the variation of reactivity with conversion profiles for all lignite samples has similar trends; it first increases up to a certain conversion, which is different for each lignite sample, then decreases with a further increase in the conversion. The authors explained the reactivity with conversion data of different ranks of coal using the results from a previous study which involved several texture characterization techniques [17] and demonstrated that lignite samples under study possessed micropores of molecular dimensions and that SAXS (Small Angle X-ray Scattering) measurement and carbon dioxide adsorption data indicated that some of these pores were closed and some were opened to larger mesopores and macropores with restricted passages [18]. It is observed that in the initial stages of the gasification disorganized carbon from tars are removed resulting in the opening of inaccessible porosity and then an increase in all sizes of pores which enhance reactivity until up to a certain conversion.…”
Section: Effect Of Coal Rankmentioning
confidence: 99%
“…However, water sorption and X-ray scattering (SAXS) methods are currently used to measure the surface area of coal (Senel et al 2001) due to high accuracy. The variation of coal physical properties with carbon content or rank is shown in Fig.…”
Section: Surface Areamentioning
confidence: 99%
“…Turkey has considerable amount of coal reserves of which lignites constitutes major portion with a reserve of 8.05 Â 10 6 tonnes [26,27] and mainly utilized conventionally for power production and heating purposes.…”
Section: Materials and Their Characterizationmentioning
confidence: 99%
“…The present study was undertaken to provide information on pyrolysis and gasification rates of lignite samples representative of four important lignite deposits in Turkey. A detailed study on the textural properties of Turkish coals including the samples used in this study was published previously [26].…”
Section: Introductionmentioning
confidence: 99%